Ethos discursivo e escrita de si: a constituição de uma comunidade discursiva em torno do gênero fanfiction - Oliveira, Adriana Figueiredo de (2015)
The fanfics (fanfiction abbreviation) constitute a contemporary discursive genre characterized by collaborative writing - through which fans of a dedicated work of fiction become coauthors of endless possibilities for further work. Their circulation is preferably made in media such as social networks and blogs, whose operating modes are coated values shared by young people in contemporary society, which appear to be, through interaction by writing and reading these fanfics, true discursive communities (MAIGUENEAU, 2008b). We search to understand, based on theoretical assumptions and analytical devices of French Discourse Analysis, subjectivities teenagers discursively constructed in fanfic "The Twilight Saga - Blue Moon". Its plot is focused on the adventures experienced by the young Renesmee, the daughter of Bella and Edward, protagonists of the "Twilight Saga" series of four books written by Stephenie Meyer which adapted for film have become a true success with the public in the West. In addition to a contribution to the discipline of discourse analysis, the research aims to raise considerations concerning mother tongue classes. The analysis allowed to grasp the features of a teenager discursive ethos in fanfic. The contributions of the philosopher Michel Foucault to discourse studies and subjective processes are also important for our research, since the analysis allowed us to see that, through the production of fanfiction and comments on it, young people perform a self-writing (FOUCAULT, 2006) that, in fact, can characterize them as belonging to a specific discourse community.